Usability Evaluation of a Google Sites-Based E-Learning Platform Using the ISO 9241-11:2018 Standard - Nurul Ikhsan; Sarmidi Sarmidi; Sulidar Fitri (International Journal Education and Computer Studies (IJECS), 2026)
This study aims to evaluate the usability of an e-learning system developed using Google Sites at SMA Negeri 6 Bengkulu Tengah based on the ISO 9241-11 standard. The evaluation focuses on two main aspects, namely effectiveness and user satisfaction. The research employed a quantitative descriptive method with data collected through questionnaires distributed to 30 students and 2 teachers. The results show that the effectiveness aspect achieved a percentage of 94.4% for teachers and 88.4% for students, both categorized as "very good." Meanwhile, the satisfaction aspect obtained 90% from teachers and 86.67% from students, also categorized as "very good." These findings indicate that the e-learning system is able to support the learning process effectively and provides a high level of user satisfaction. Therefore, the Google Sites-based e-learning platform can be considered feasible and useful as a learning medium in the school environment.